Raptor communities in hill habitats in south-eastern Zimbabwe - Davison, Bruce (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1998)
The interrelationships between species composition, resource-use and availability, breeding and competition were studied in two hill habitat raptor communities in a conserved reserve and an unprotected communal land in Zimbabwe in 1995 and 1996. The conserved Lonestar Study Area (LSA) and the unprotected Communal Land Study area (CLSA) had 38 and 31 raptor species, high and normal diversities for the area sizes respectively. An estimated 147 pairs of 21 raptor species bred in 40km² in the LSA compared to only 26 pairs of 22 raptor species per 40km² in the CLSA. Six species (African Hawk Eagle Hieraaetus spilogaster, Black Eagle Aquila verreauxii, Crowned Eagle Stephanoaetus coronatus, Little Banded Goshawk Accipiter badius, Barn Owl Tyto alba,and Barred Owl Glancidium capense made up 69% of breeding raptors in the LSA, while African Hawk Eagles, Little Banded Goshawks, Barn Owls and Barred Owls made up 58% of the breeding raptors in the CLSA. The abundance of Black, Crowned and African Hawk Eagles in the LSA was linked to abundant hyrax, Heterohyrax brucei and Procavia capensis and juvenile bushbuck Tragelaphus prey, and the high reproduction rates of Natal Francolin Francolinus natalensis (0.7 per ha when not breeding). Little Banded Goshawk and Barn Owl abundances were linked to their ability to change prey preferences according to prey availability. A fairly high rate of breeding attempts by eagles in the LSA in both years (60 - 76% of all pairs per year)was probably also linked to prey abundance, Most breeding failures were predator related, and were more common in areas of relatively low nesting densities indicating lower parental vigilance there. High eagle breeding densities were associated with small mean territory sizes in the LSA (7.7 - 10.7km² for the main eagle species). Eagles in the LSA usually nested closer to another eagle species than a conspecific, resulting in regular distributions of nests and no territory overlap within species. Differences in daily flight activity of eagles in both study areas, and in the onset of breeding between LSA eagles probably reduced interspecific aggression. Interspecific competition food and nest sites amongst LSA eagles was possibly lessened by slight ditferences in resource selection. Raptor resources were mostly unaffected by human activities in either study area during the study period. Differences in the raptor communities were probably as a result of natural habitat differences. The CLSA raptors potentially face resource loss through forest clearing and hunting. An expansion of the present CAMPFIRE program will protect the CLSA raptors.
Keywords: Birds of prey -- Zimbabwe; Birds of prey -- Ecology -- Zimbabwe